(untitled) (Veterinary Science, 2017)
The objective of this trial was to evaluate the preventive effects of foot bath technique and immunization on interdigital necrobacillosis incidence in beef cattle grazing alfalfa pasture. The work was carried out in a farm with antecedents of high incidence of interdigital necrobacillosis (IN) and lasted from 10/10/98 until 03/15/99. Four hundreds Hereford steers were alloted to two groups of 200 animals: without foot bath (WFB) and with foot bath (FB). The food bath solution contained formaldehyde (2 % in water) and copper sulfate (2 % in water). The treatment was applied every 2 to 3 weaks. The bovines stayed 10 minutes in a concrete foot bath, with a 15-20 animals capacity. In each group, 100 animals received two doses of a commercial vaccine against IN. Then, the four groups formed were: WFB-WV, WFB-V, FBWV and FBV. All groups grazed in the same parcel of pasture and were handled in the same facilities. The incidence of IN on each group was 14, 15, 3 y 5. The results of this trial was compared with the X 2 test and it was observed a statistically very significant effect (p0.01) of foot bath treatment and a null effect of the vaccine